PENGARUH PENERAPAN STRATEGI AKTIF TIPE GROUP TO GROUP DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 AMPEK NAGARI LUBUK BASUNG - Nengsih, Neno; Rahmi, Rahmi; Yunita, Alfi (Pendidikan Matematika, 2013)
This research is backgrounded by the lack of understanding of mathematical concepts and students prefer to ask other students Students more quiet deep lawsuit handcuffing. This research aims to know is students understanding of mathematical concepts by applying active learning strategies Group to Group with LKS type better than student understanding of mathematical concepts by applying conventional learning. This research is experimental, with random designs on the subject. The population in this research were all students of class VIIIÂ  SMPN 1 Ampek Nagari Lubuk Basung. The selected sample class VIII.5 class as the experimental class and the control class VIII.3 class. The instrument that used in this research is the final test in the form of essay with the reliability test was 0.456. Based on the analysis of data obtained by the average outcomes of student learning in experimental class was 77,79 bigger than the control class 67,68. hypothesis testing using t-test with the help of MINITAB, obtained p-value = 0.021 is smaller than Î± = 0.05. It can be concluded that the students understanding of mathematical concepts by applying active learning strategies Group To Group with LKS type better than student understanding of mathematical concepts with conventional learning.